2014
DOI: 10.1002/2013jd021021
|View full text |Cite
|
Sign up to set email alerts
|

Key parameters controlling OH‐initiated formation of secondary organic aerosol in the aqueous phase (aqSOA)

Abstract: Secondary organic aerosol formation in the aqueous phase of cloud droplets and aerosol particles (aqSOA) might contribute substantially to the total SOA burden and help to explain discrepancies between observed and predicted SOA properties. In order to implement aqSOA formation in models, key processes controlling formation within the multiphase system have to be identified. We explore parameters affecting phase transfer and OH(aq)-initiated aqSOA formation as a function of OH(aq) availability. Box model resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
140
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(159 citation statements)
references
References 111 publications
8
140
2
Order By: Relevance
“…H 2 O 2 is an important participant in aqueous-phase chemistry [Ervens et al, 2014] and can be a major precursor of plant-damaging reactive oxygen species [Nguyen et al, 2015]. The measured H 2 O 2 v d of 4.7 ± 0.4 cm s…”
Section: 1002/2015gl065839mentioning
confidence: 92%
“…H 2 O 2 is an important participant in aqueous-phase chemistry [Ervens et al, 2014] and can be a major precursor of plant-damaging reactive oxygen species [Nguyen et al, 2015]. The measured H 2 O 2 v d of 4.7 ± 0.4 cm s…”
Section: 1002/2015gl065839mentioning
confidence: 92%
“…For this estimation, models describing the multiphase cloud chemistry have been developed and have considered the reactivity in the gas and aqueous phases along with the mass transfer between the two phases (Ervens et al, 2014;Long et al, 2013;Tilgner and Herrmann, 2010). These numerical tools allow for the estimation of the steady-state concentration of HO q ([HO q ] ss ), which is a crucial quantity to understand the fate of atmospheric pollutants (Arakaki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A number of ground-based and airborne field studies have found a close correlation between oxalic acid and sulfate in ambient particles and cloud droplets, relating aqueous-phase chemistry to the formation of oxalic acid in aerosols and cloud droplets (Yao et al, 2002(Yao et al, , 2003Yu et al, 2005;Sorooshian et al, 2006Sorooshian et al, , 2007aMiyazaki et al, 2009;Wonaschuetz et al, 2012;Wang et al, 2016). In recent years, several model and laboratory studies have suggested that the aqueous-phase oxidation of highly water-soluble organics like glyoxal, methylglyoxal and glyoxylic acid can efficiently produce oxalic acid in aerosol particles and cloud droplets (Lim et al, 2010;Myriokefalitakis et al, 2011;Ervens et al, 2014;Yu et al, 2014;McNeill, 2015). Recent stable carbon isotope studies and field observations have also suggested that oxalic acid forms through aqueous-phase reactions (Wang et al, 2012;Cheng et al, 2015).…”
mentioning
confidence: 99%